Analytical and numerical approaches for calculating the static deflection of functionally graded beam under mechanical load - Z. Zainy, Hayder; S.Al-Ansari, Luay; M.Al-Hajjar, Ali; M.S.Shareef, Mahdi (International Journal of Engineering and Technology, 2018)
Functionally graded material is a new type of composite material and it is used in several smart applications. The static deflec-tion of the FG beam under mechanical and/or thermal load is a complex phenomenon because of the complexity of material properties. The power law model is used to described the material properties of FG beam. The analytical approach depending on the compound beam theory is derived in order to find the equivalent cross section area of FG beam and then calculate the static deflection for new beam. This approach can be achieved analytically when the power law index equals 1 and achieved by numerical integrals (Trapezoidal and Simpson Method) for any value of power law index. The numerical approach ( Finite Element Method using ANSYS software) used in this work depends on the laminate theory , compound beam theory in order to build three different models. The validation of these methods were done by comparing the results with the results of Alexraj et. al. [9]. The comparison among the five methods were done and analysis to choose the suitable method.Â Â